Minecraft : combat handbook - Milton, Stephanie; Soares, Paul (Writer on computer games); Cordner, Theo; Bolder, Joe; FyreUK; CNB Minecraft (New York, NY : Scholastic, 2015)
"Revised edition with the most up to date stats, info, and sixteen pages of brand-new material! In Minecraft, you're never alone and the threat of attack is constant. How will you survive? The Official Combat Handbook now has sixteen additional pages with brand-new content. This book will teach you everything you need to know to defend yourself from hostile monsters and enemy players. You can learn how to build a fort, craft armor and weapons, set mob traps, defeat your enemies in one-on-one combat, and battle your way out of the Nether and the End. With tips from Minecraft experts, developer Jeb, and creator Notch himself, you'll be a Minecraft warrior in no time!" -
Includes bibliographical references (page 95)
Keywords: Minecraft (Game) -- Handbooks, manuals, etc. -- Juvenile literature; Video games -- Handbooks, manuals, etc. -- Juvenile literature; Computer adventure games -- Juvenile literature